Prevalence of kidney disease and associated factors among adults with chronic hepatitis B virus in Southwestern Uganda - Samuel Jjunju; Edwin Nuwagira; Mike Ssemusu; Grace Kansiime; Conrad Muzoora (Annals of Medicine and Surgery, 2026)
Background: Hepatitis B virus (HBV) is a global health problem endemic in Sub-Saharan Africa, with 65% of global cases occurring in the WHO Western Pacific and African regions. HBV is a known primary cause of kidney disease that progresses throughout the illness. Early detection of kidney disease and antiviral initiation can slow its progression. Our study aimed to identify the prevalence of kidney disease and associated factors in adults with chronic HBV. Methods: We conducted a cross-sectional study from November 2023 to December 2024 in Mbarara, Uganda, recruiting adults with chronic hepatitis B. Data collected: socio-demographics, comorbidities, coinfections, and hepatitis B-related data. Spot urine and blood were collected for dipstick, urine neutrophil gelatinase–associated lipocalin (NGAL), and creatinine with estimated glomerular filtration rate (eGFR). We defined kidney disease as the presence of (1) urine NGAL >132 ng/mL, (2) eGFR <60 mL/min/ 1.73 m2 or (3) eGFR between 60 and <90 mL/min/1.73 m2 with proteinuria or hematuria. We utilized logistic regression to determine factors associated with kidney disease. Results: We enrolled 157 participants with a mean age of 35.8 (standard deviation, ±12.5) years, and 50% (79/156) were males. Overall kidney disease prevalence was 27% (43/157; 95% confidence interval (CI): 20.6–35.1%). Prevalence based on urine NGAL was 17.2% (27/157; 95% CI: 11.6–24.0), eGFR <60 mL/min/1.73 m2 was 5.7% (9/157; 95% CI: 2.7–10.6), and eGFR between 60 and <90 mL/min/1.73 m2 with either proteinuria or hematuria was 9.6% (15/157; 95% CI: 5.4–15.3). Being female was associated with higher odds of kidney disease (adjusted odds ratio, 2.49; 95% CI: 1.16–5.36; P = 0.019). Conclusion: Nearly one-third of adults with chronic Hepatitis B in Uganda had kidney disease, with NGAL increasing the detection by 12% over creatinine and urine dipstick alone. We recommend frequent monitoring of kidney function in adults with chronic HBV.
Keywords: chronic hepatitis B virus; kidney disease; neutrophil gelatinase–associated lipocalin